Criticality, Teacher Identity, and (In)equity in English Language Teaching Issues and Implications (Educational Linguistics, 2018)
This edited volume, envisioned through a postmodern and poststructural lens, represents an effort to destabilize the normalized "assumption" in the discursive field of English language teaching (ELT) (Pennycook, 2007), critically-oriented and otherwise, that identity, experience, privilege-marginalization, (in)equity, and interaction, can and should be apprehended and attended to via categories embedded within binaries (e.g., NS/NNS; NEST/NNEST). The volume provides space for authors and readers alike to explore fluidly critical-practical approaches to identity, experience, (in)equity, and interaction envisioned through and beyond binaries, and to examine the implications such approaches hold for attending to the contextual complexity of identity and interaction, in and beyond the classroom. The volume additionally serves to prompt criticality in ELT towards reflexivity, conceptual clarity and congruence, and dialogue. .